The Global Financial Crisis : Impact on WAEMU Member Countries and Policy Options - Mueller, Johannes (IMF Staff Position Notes; Staff Position Note ;, 2009)
Most WAEMU countries are likely to see economic growth deteriorate over the next two years as a result of the global economic crisis, and some WAEMU countries will be more severely affected by the crisis than others. This could have a detrimental effect on efforts to reduce poverty. Deteriorating remittances and commodity export prices are projected to negatively affect the WAEMU countries' external current account deficit and reserves, although the impact should be cushioned by positive terms-of-trade shocks, such as declining import prices for food and fuel products. These developments should also help lower inflation pressures, bringing WAEMU inflation closer to its historical level of about 2 percent by 2010.